Isolation and Characterization of Protein Tyrosine Phosphatase 1B (PTP1B) Inhibitory Polyphenolic Compounds From Dodonaea viscosa and Their Kinetic Analysis - Uddin, Zia; Song, Yeong Hun; Ullah, Mahboob; Li, Zuopeng; Kim, Jeong Yoon; Park, Ki Hun (Frontiers in Chemistry, 2018)
Diabetes mellitus is one of a major worldwide concerns, regulated by either defects in secretion or action of insulin, or both. Insulin signaling down-regulation has been related with over activity of protein tyrosine phosphatase 1B (PTP1B) enzyme, which has been a promising target for the treatment of diabetes mellitus. Herein, activity guided separation of methanol extract (95%) of Dodonaea viscosa aerial parts afforded nine (1-9) polyphenolic compounds, all of them were identified through spectroscopic data including 2D NMR and HREIMS. Subsequently, their PTP1B inhibitory potentials were evaluated, in which all of the isolates exhibited significant dose-dependent inhibition with IC50 13.5-57.9 μM. Among them, viscosol (4) was found to be the most potent compound having IC50 13.5 μM. In order to unveil the mechanistic behavior, detailed kinetic study was carried out, in which compound 4 was observed as a reversible, and mixed type I inhibitor of PTP1B with inhibitory constant (Ki) value of 4.6 μM. Furthermore, we annotated the major metabolites through HPLC-DAD-ESI/MS analysis, in which compounds 3, 6, 7 and 9 were found to be the most abundant metabolites in D.viscosa extract.